2009
DOI: 10.1254/jphs.08328fp
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Activated Aryl Hydrocarbon Receptor–Induced Transcriptional Activation by 5α-Dihydrotestosterone in Human Prostate Cancer LNCaP and Human Breast Cancer T47D Cells

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) and dioxins are ubiquitous environmental pollutants and activate the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor. It has been reported that testosterone represses 2,3,7,8-tetrachlorodibenzo-p-dioxininduced transcription of the cytochrome P450 (CYP) 1A1 gene in LNCaP cells. In this study, we investigated the mechanism for the repression of 3-methylcholanthrene (3MC)-induced transcription of AhR-regulated genes, CYP1A1, CYP1A2, CYP1B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…However, the inhibitory effect of DHT was abolished by knockdown of the androgen receptor protein with siRNA. It was determined that DHT induced heterodimerization between AR and AhR when cells were also treated with an AhR agonist [48]. The data presented here, reveals that AhR can modulate proliferation of prostate cancer cells in the absence of androgen receptor.…”
Section: Discussionmentioning
confidence: 57%
“…However, the inhibitory effect of DHT was abolished by knockdown of the androgen receptor protein with siRNA. It was determined that DHT induced heterodimerization between AR and AhR when cells were also treated with an AhR agonist [48]. The data presented here, reveals that AhR can modulate proliferation of prostate cancer cells in the absence of androgen receptor.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, we could not find androgen receptor (AR)-binding element in the spacer region. Recently, it has been suggested that complex formation between activated AR and AhR plays an important role in suppression of the AhR-mediated transcription of CYP1 family genes (Sanada et al 2009). Therefore, the androgen-mediated down-regulation observed in this study is thought to occur, at least in part, through a complex formation between AR and AhR.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inclusion of TCDD blocked androgen-dependent cell proliferation in cell culture [40]. A mechanism for the cross-talk was proposed where the androgen receptor and the AHR form a complex, altering transcription [41]. Further studies showed that activated AHR decreased the protein level of androgen receptor through an increase in targeted protein degradation through an E3 ubiquitin ligase complex in prostate cancer cells [42].…”
Section: Discussionmentioning
confidence: 99%